Imagined Spaces Through Public Space Typography: Preliminary Studies Using Multimodal Ethnography - Putra, Wibisono Tegar Guna; Apsari, Diani (Jurnal Bahasa Rupa, 2022)
Text cannot be separated from its context, nor can the complexity of reality be reduced. The relationship of the text as a visual element between the imagined spaces that follow is what this study tries to explain further. In this article, the authors choose the quote, "Bumi Pasundan Lahir Ketika Tuhan Sedang Tersenyum" / (English: "Bumi Pasundan was created when God was smiling") which is classified as public space typography as the object of research. This discussion uses multimodal ethnography as a data search tool that will be analysed using discourse analysis to answer how quotes, as visual elements, are reproduced and depicted as a "beautiful" space through social media, creating a specific image of the imagined space.